Stress, Psychopathological Symptoms and Risk of Clicking in College Students: A Case-Control Study (2015)
scientific evidence suggests that stress and psychological symptoms play an important role on diseases. The aim of this study was to investigate clicking in individuals with stress and different psychopathological symptoms.